Adenocarcinoma of the sphenoid sinus - Darouassi, Youssef (Pan Afr Med J, 2014)
Adenocarcinomas of the sphenoid sinus are exceptional. In this paper, we report a new case with a review of the literature. Our patient was a 45-year-old man who presented with isolated retro orbital headache. CT and MRI suspected a malignat tumor of the sphenoid sinus. The patient underwent a debulking surgery. The final pathology carried out the diagnosis of primary adenocarcinoma. The patient died several months later from radiotherapy complications. Even if adenocarcinomas of the sphenoid sinus are exceptional, they should be considered in the differential diagnosis of sphenoid sinus masses. The prognosis is poor.